Analisis Pertimbangan Hakim mengenai Wanprestasi dalam Perkara Perjanjian Kredit di Tiga Tingkatan Peradilan: Analisis Pertimbangan Hakim mengenai Wanprestasi dalam Perkara Perjanjian Kredit di Tiga Tingkatan Peradilan - Suleng, Suleng Belista; Pratama, Rio Arif (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2025)
This study aims to examine the legal considerations of judges in cases of default in credit agreements and their impact on legal protection for parties who suffer losses. This study focuses on three decisions: Surabaya District Court Decision No. 714/Pdt.G/2021/PN Sby, Surabaya High Court Decision No. 695/Pdt/2022/PT Sby, and Supreme Court Decision No. 2149 K/Pdt/2024. The method applied is normative juridical research using a case approach. The research findings indicate differences in considerations between the first instance and cassation courts, which stated that the defendant was in default, while the appellate court held the opposite opinion. The Supreme Court corrected the considerations at the appellate level and provided legal protection to the plaintiff as the party who had fulfilled the contractual obligations. The decision also confirmed that liability for default can be imposed on creditors who are negligent in carrying out their obligations. The implications of this decision underscore the importance of protecting parties in good faith and affirming the role of judges in correcting injustices in contracts.